Haemostasis in Spine Surgery
DOI: 10.1007/3-540-27394-8_19
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of post-operative shed blood: laboratory characteristics and clinical utility

Abstract: IntroductionIt is well known that the defence mechanisms provided by the immune system can be altered by traumatic injury, surgery and transfusions, and there is a growing interest for acquiring greater knowledge on the causes and mechanisms involved in the immunodepression induced by the anaesthetic-surgical procedure, since this increases the susceptibility to post-operative infection and tumour relapse after potentially curative surgery [15, 19,62]. This interest further increases when it is seen that, in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…[1][2][3][4][7][8][9][10][11][12][13][14][15] To date there has been no direct comparison between post-and intraoperative blood salvage. In 1995 Huo et al showed intraoperative blood salvage to be more efficient in reducing blood loss in total hip replacements than ABT drains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][7][8][9][10][11][12][13][14][15] To date there has been no direct comparison between post-and intraoperative blood salvage. In 1995 Huo et al showed intraoperative blood salvage to be more efficient in reducing blood loss in total hip replacements than ABT drains.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]8 Both intraoperative blood salvage and postoperative retransfusion drains have been shown to be effective in reducing blood loss in total hip arthroplasties. [1][2][3][4][7][8][9][10][11][12][13][14] Intraoperative cell salvage involves collection of blood lost during surgery using a suction device. The blood is centrifuged and washed so that only concentrated red cells are collected and returned to the patient.…”
mentioning
confidence: 99%
“…In addition, the retrospective study design [11], the comparison of a prospective study group with a retrospective control group [22], or the missing randomization procedure in a prospective published trial [7], all postulating a lower ABT rate for the reinfusion group, are critical limitations and therefore not directly comparable to our prospective, randomized study. Some previous studies that have noted only a small or no benefit in reducing the need for postoperative ABT evaluated a retransfusion device for USB [17,18,23,30]. Even when trials reported a lower ABT rate for the autologous retransfusion group, they either found no difference in administered ABT units per patient [7,20,34] or the ABT number per patient transfused was not analyzed [11,22,34] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In general, retransfusion devices can be divided in two major groups: systems for unwashed shed blood (USB) and systems for washed shed blood (WSB) [21,23]. Owing to the higher related risk of a transfusion reaction to USB (compared with WSB), some authors [12,35,39,40] advise washing the shed blood before retransfusion.…”
Section: Introductionmentioning
confidence: 99%
“…4,9 Salvaged, unwashed blood has been shown to be substandard, as it is diluted and may contain a high concentration of hemolyzed red blood cells, cytokines and clotting factors. 10 Further risks with the reinfusion of hemolyzed blood include renal failure; disseminated intravascular coagulation (DIC) due to activated clotting or fibrinolytic factors; and risk of fat embolism due to debris, such as fat particles. [10][11][12] Contemporary cell salvage allows for effective reduction of contaminants by cell separation and washing, resulting in an autologous red blood cell concentrate of normal function and viability.…”
mentioning
confidence: 99%